Board Examination Analytics for Pamantasan ng Cabuyao, Laguna - Hernandez, Gloria; Dela Cruz, Ramiro; Marucot, Emmanuel (JPAIR Multidisciplinary Research, 2020)
This study provides a framework for determining board exam probabilistic performances of students through the identification and analysis of indicators that affect student board exam performances. The design and development of the framework are governed by the theoretical and empirical study of factors related to student profiles, academic metrics, and academic support services metrics. The formulation of factors and considerations for the framework revolves around the identification of causal items affecting the board exam performance of examinees. The factors are tested for their perceived causative and relational effects as drawn from related studies and literature. Moreover, this study provides a framework that addresses the issues related to managing board examination course offerings via consideration of university policies, practices, priorities, and programs.